Conservation and reconstruction of art paintings of the late nineteenth century in the lobby of the academic building of L’viv Polytechnic National University - Bevz, Mykola; Hetmanchuk, Serhiy (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
The research of artistic decoration and practical works of restoration of wall paintings of the main lobby of former building of the Galician Highest Regional Court presented in the article. The building used today as academic korp for the needs of L’viv Polytechnic National University. The first part of the restoration work was carried out in this building during 2012−2014 years.